Ujváry Béla, Göőz József, Petróczy István (iratok) - Ujváry Béla, Göőz József, Petróczy István (Fond 4 Lampel [Wodianer] Könyvkiadó Vállalat irattára, 1908)
Fond 4 Lampel [Wodianer] Könyvkiadó Vállalat irattára